Was am Herzen nagt und auf die Nerven geht - Kristen, Arnt (Der Internist, 2018)
Transthyretin is a transport protein for thyroxine and retinol-binding protein, which is mainly produced in the liver. Hereditary transthyretin-related amyloidosis (ATTR) is caused by one of more than 120 point mutations in the transthyretin gene and inherited as an autosomal dominant disorder. The mutations cause a reduction in the stability of the tetrameric structure and dissociation into dimers and monomers as the rate-limiting step in amyloid formation is promoted. Clinical symptoms are related to the specific mutation, the age of onset, the ethnic background and environmental factors. The nerves, heart, eyes and intestines are paticularly affected. In general, two different age peaks are observed. An accumulation occurs at the age of 25-35 years with predominantly neurological symptoms. The second peak occurs between the ages of 55 and 65 years and is commonly associated with cardiac involvement with or without polyneuropathy. Characteristic for the nerve involvement are the symmetrical small fiber polyneuropathy and an autonomous polyneuropathy. The typical picture of cardiac involvement is biventricular hypertrophy with diastolic dysfunction finally resulting in restrictive cardiomyopathy. In addition to the symptomatic treatment for the alleviation of individual organ disorders, for many years liver transplantation was the only causal therapy of ATTR amyloidosis. Since 2011 tafamidis, a highly selective transthyretin stabilizer, has been the first drug approved for treatment of ATTR resulting in reduction of the progression of polyneuropathic symptoms. Other therapeutic approaches to reduce amyloid formation (patisiran and inotersen) effectively reduce transthyretin blood levels, leading to a reduction in polyneuropathy and improved quality of life. The approval is expected in 2018.
Gesehen am 30.10.2019